The Socio-Economic Life of the People of Nagari Mandeh, 2015–2023 - Junesta Ruksah; Meri Erawati; Juliandry Kurniawan Junaidi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the socioeconomic life of the community in Nagari Mandeh from 2015 to 2023, which has undergone changes alongside the development of the Mandeh Integrated Marine Tourism Area (KWBT). The study aims to understand the community’s socioeconomic life and the impact of tourism development on their lives. The research employs a historical methodology through four stages: heuristics, source criticism, interpretation, and historiography. Research sources were obtained through interviews with fishermen, tourism business operators, lodging owners, boat operators, community members, and village officials, and were supported by archives, data from the Central Statistics Agency (BPS), the South Pesisir Regency Department of Tourism, Youth, and Sports, documentation, and bibliographic sources. The results indicate economic changes driven by the emergence of tourism transportation services, food stalls, lodging, trade, and dual employment involving both fishing and tourism. The COVID-19 pandemic temporarily hampered tourism activities and the marketing of fish catches. The development of tourism has also influenced patterns of interaction, family involvement, household conditions, and lifestyles, without eliminating the spirit of mutual cooperation. Thus, the community has been able to adapt to the development of tourism without abandoning the character of coastal life.